Characteristics and Controlling Factors of Natural Fractures in Lacustrine Mixed Shale Oil Reservoirs: The Upper Member of the Lower Ganchaigou Formation in the Ganchaigou Area, Qaidam Basin, Western China - Xing Zhao; Guiwen Wang; Dong Li; Song Wang; Quanwei Sun; Jin Lai; Zongyan Han; Yafeng Li; Yinghao Shen; Kunyu Wu (Energies)
Natural fractures within the lacustrine mixed shale oil reservoirs of the upper member of the Lower Ganchaigou Formation (E32) in the Ganchaigou area of the Qaidam Basin are pivotal to the exploration and development of shale oil and gas. This research investigates the developmental characteristics and controlling factors of natural fractures and their impact on the reservoir quality based on cores, image logs, thin sections, scanning electron microscopy observations, and experimental and production data. The results indicate that natural fractures in the E32 are categorized into tectonic fractures, diagenetic fractures, and abnormal high-pressure fractures. Tectonic fractures are characterized by a significant variation in dip angles, a wide range of apertures, low density, and a high filling degree. Diagenetic fractures typically exhibit low dip angles, small apertures, high density, and a low filling degree. Abnormal high-pressure fractures display chaotic orientations and complex styles, often consisting of filled fractures. The development and distribution of natural fractures are jointly influenced by mineral composition and brittleness, lamination structure, organic matter content and maturity, diagenesis, tectonic factors, and abnormal high pressure. A high content of dolomite, thin-bedded structures comprising carbonate laminae and felsic laminae, and abundant mature organic matter provide a favorable foundation for fracture development. Diagenesis, including dissolution, pressure solution, and mineral dehydration shrinkage, acts as a beneficial guarantee for fracture development. Tectonic locations near the hanging wall of faults and the core of anticlines are the main regions for fracture development. Abnormal high pressure is a crucial driving force for fracture development. Interconnected natural fractures of various types and scales significantly expand reservoir space and enhance pore connectivity and flow capacity, serving a vital function in maintaining high and stable production in lacustrine mixed shale oil reservoirs.